The V4 – ASEAN Perspectives Cooperation and Diplomatic Missions in Southeast Asia and Central Europe - Laš, Lukáš (Rethinking Asia in World Politics, 2023)
This paper provides an overview of diplomatic missions between Central Europe and Southeast Asia and draws a picture of the political, economic, and cultural interactions between the countries of the two regions on vertical and horizontal levels. Desktop research is combined with selected theoretical views on diplomatic representation and international cooperation. A particular attention is paid to the interaction of the Visegrad Group (V4) countries with the countries of the Association of Southeast Asian Nations (ASEAN). Descriptive empirical views are interpreted in a growing “Indo-Pacific” context. The potential of the V4-ASEAN cooperation format is recognized but not yet fulfilled, which is expected to change with implementation of the EU’s Indo-Pacific Strategy.